Assessing the effect of land use on the Higher Education Institution development by using/integrating Geographical Information System (GIS) and Remote Sensing (RS) data/approach for land suitability analysis / Siti Khadijah Anuar ... [et al.] - Anuar, Siti Khadijah; Salleh, Nor Aini; Mohd Mokhtar, Munirah Radin; Abdullah Sani, Suwaibatul Islamiah (2022)
Developed area is an indicator to depict the growth of an area in terms of economical aspect and social interaction among the locals due to the establishment of higher education institution. However, before developing a new area, local authority need to find or locate a suitable location where it can be done. This study is carried out by focusing on two (2) objectives: (i) to identify the growth development pattern for the past 20 years within the area of Seri Iskandar, Perak and (ii) to determine suitable area for urban development by using GIS based technique and remote sensing. With the help of Geographical Information System (GIS) and Remote Sensing (RS), land use or land change around Seri Iskandar, Perak will be determined by using the data from year of 1999 to 2019. Satellite images will be processed to investigate the land use or land changes in Seri Iskandar, Perak. The land use or land change will be ascertained by categorising them into developed area, mixed agriculture, water bodies, bare soil, vegetation, cloud and forest. Therefore, this study can assist the local authority in making a proper planning for urban development in Seri Iskandar, Perak. The influence of establishing a university may be estimated by looking at the land use patterns and population growth in the Seri Iskandar town area. Besides that, it can help agencies such as Department of Town Planning and private companies in determining which site or land can be used for development purpose.